The role of trumpet musical aesthetics in Movement II of Bandung marching band: An analysis in “Bandung 1946” - Andios Resiok Topa; Davin Permana Putra (Universitas Pendidikan Indonesia, 2023)
This study examines the influence of trumpet musical aesthetics in Movement II of the Bandung Marching Band